Pengaruh Media Buku Cerita Terhadap Kemampuan Membaca Pemahaman Siswa Kelas III di SDN 1 Kalibuntu - Wulan Sari; Nugraha Permana Putra; Asih Wahyuningsih (CV. ULIL ALBAB CORP, 2024)
Learning activities are designed to provide new experiences and provide learning for students, to build mental and physical through interactions between students, teachers and the school environment and other learning resources, in order to achieve basic competencies. Teachers are the determining factor for the level of success in classroom learning. Some teachers still use classic and undeveloped learning methods, so that it affects the results that are less than optimal. The purpose of this study was to determine how the effect of Indonesian language learning with storybook media on reading comprehension of grade III students at SDN 1 Kalibuntu. This research design uses the one group research method where the research is conducted with one class. The research was conducted at SDN 1 Kalibuntu on grade III students with a sample size of 26 students. In the even semester, the researcher conducted a study which began by giving an initial test (pretest) and then applying the Indonesian language learning method using storybook media and after that the final test (posttest) was carried out. The results of this study show a sig value (2-Tailed) of 0.000 while the significance level is 5% or 0.05 or sig value <0.05 then H1 is accepted. So it can be concluded that learning Indonesian using storybook media has a significant effect on students' reading comprehension skills in class III at SDN 1 Kalibuntu.